Mother’s knowledge and attitudes regarding poliomyelitis eradication among a sample in Bab Al Muadham health centre in Baghdad city, Iraq - Entsar Khaleel Sameen; Shatha Mahmood Niazy; Asmaa Ibadi Salman; Sahar Al Kareem Alabbas Al Ghnaimawi (Journal of the Pakistan Medical Association, 2023)
Objective: To determine knowledge and attitude and practice of mothers towards poliomyelitis vaccination. Method: The cross-sectional study was conducted from October 2019 to March 2020 at Bab Al-Moadham Health Centre, Baghdad, Iraq, and comprised mothers regardless of age who were visiting the child care unit with at least 1 child aged <5 years. Data was collected through a questionnaire. Data was analysed using SPSS 10. Results: There were 150 mothers with a mean age of 31.08±9.31 years. The largest age group was 20-29 years 90(60%) (p<0.05). There were 100(66.6%) subjects from urban areas, and 67(44.6%) had at least a college degree (p<0.05). The most common source of information was television 110(73.3%), and 135(90%) subjects agreed that polio vaccine for the child was a necessity. Overall assessment of the sample was good, with a percentile global means of the score value of 50.30±9.81. Conclusion: Urban, educated and working mothers aged 20-29 years were more knowledgeable about polio than the rest. Keywords: Health, Knowledge, Attitudes, Poliomyelitis, Vaccination, Eradication.